Accepting Inequality Deters Responsibility: How Power Distance Decreases Charitable Behavior - Winterich, Karen Page; Zhang, Yinlong (Journal of Consumer Research, 2014)
Abstract Could power distance, which is the extent that inequality is expected and accepted, explain why some countries and consumers are more likely to engage in prosocial behavior, including donations of both money and time? This research proposes that higher power distance results in weaker perceptions of responsibility to aid others, which decreases charitable behavior. Both correlational and causal evidence is provided in a series of five studies that examine country-level power distance as well as individual and temporarily salient power distance belief. Consistent with the mediating role of perceived responsibility, results reveal that uncontrollable needs and communal relationship norms are boundary conditions that overcome the negative effect of power distance on charitable behavior. These results explain differences in charitable giving across cultures and provide implications for nonprofit organizations soliciting donations.